(untitled) (IAHS Medical Journal, 2025)
Bacground: Due to the physiological changes during pregnancy, pregnant women are likely to develop recurrent Urinary Tract Infections (UTIs) and pyelonephritis, which may result preeclampsia and adverse obstetric outcomes, including prematurity and low birth weight. Pregnant women should be screened for the presence of bacteriuria early in pregnancy. This study employed a cross-sectional analysis of the presence, bacterial profile and risk factors associated with UTI among pregnant women attending antenatal check-ups. Materials and methods: This observational study was conducted at the Department of Obstetrics and Gynaecology and Clinical Pathology, Institute of Applied Health Sciences (IAHS) Chattogram during the period from January to December 2021. Sociodemographic data, obstetrical history and personal hygiene information were obtained using a well-structured questionnaire. Afterward, clean catch mid-stream urine samples were collected from 104 pregnant women. Isolation and identification of bacteria was done by conventional culture method. Results: Among the study samples, 31(29.8%) showed positive culture result and considered as confirmed UTI. E.coli (45.10%) was predominant isolated bacteria followed by klebsiella spp. (25.80%). The result of multivariate analysis revealed that pregnant women with UTI had a history of lower abdominal pain which was 4.9 times more observable then other symptoms. The odds of having UTI among pregnant women who had previously indwelling catheter were 19.1 times higher than the odds in pregnant women who had not previously indwelling catheter [p=0.023]. Conclusion: The current findings demonstrate that a high occurrence of UTIs exists among pregnant women, with significant bacteriuria in asymptomatic cases. Escherichia coli was the most predominant bacteria isolated. Routine screening for asymptomatic bacteriuria in early pregnancy is effective in preventing the occurrence of symptomatic UTIs and complications in pregnancy. IAHS Medical Journal Vol 7(2), December 2024; 36-41